The charming life of Izzy Malone - Lundquist, Jenny (Aladdin, 2016)
Izzy Malone is challenged to participate in unconventional manners-themed exercises after being enrolled in a home-study etiquette school. Each time she performs one of the assigned tasks, she will earn a charm for a charm bracelet. But when a task goes seriously wrong, can Izzy find some friends to help her make things right?